The Influence of Organizational Culture, Training, and Human Resource Development on Performance Evaluation and Energy Saving Behavior in the Engineering Department at Plaza Blok M - Widyasmoro, Adi; Madiistriyatno, Harries; Nurakhim, Bambang; Budianto, Irawan (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the influence of Organizational Culture (X1) and Training and Human Resource Development (X2) on technicians’ Energy-Saving Behavior (Y), with Performance Evaluation (Z) acting as a mediating variable. The research adopts a quantitative approach using a Likert-scale questionnaire administered to 51 respondents from the Engineering Department at Plaza Blok M. The results indicate that Training and Human Resource Development (X2) has a positive and significant effect on Energy-Saving Behavior (Y) with statistical values (β = 0.495; t = 2.814; p < 0.05). Meanwhile, Organizational Culture (X1) does not have a direct significant effect on Energy-Saving Behavior (Y) (β = 0.109; p > 0.05). Furthermore, Performance Evaluation (Z) significantly influences Energy-Saving Behavior (Y) (β = 0.332; p < 0.05). The coefficient of determination (R²) shows that the independent variables explain 58.8% of the variance in Performance Evaluation (Z) and 68.2% of the variance in Energy-Saving Behavior (Y). The mediation test results reveal that Performance Evaluation (Z) does not mediate the relationship between Training and Human Resource Development (X2) and Energy-Saving Behavior (Y), as indicated by the insignificant mediation effect (p > 0.05). This study contributes to the development of knowledge by proposing an integrative model that links human resource management systems with employees’ energy-saving behavior in commercial building operations.